Immunogenicity assessment of monoclonal antibody products: A simulated case study correlating antibody induction with clinical outcomes. Issue 5 (September 2015) - Knezevic, Ivana; Kang, Hye-Na; Thorpe, Robin
Abstract: Monoclonal antibodies are large molecules with complex structure and functions. They have a wide application for treatment of a broad range of chronic diseases and represent the largest class of biotherapeutic products. Given that biotherapeutic products may induce unwanted humoral and/or cellular immune responses in recipients, it is essential to investigate the immunogenicity of a product prior to licensure. The immune response is influenced by many factors and data generated in the pre-licensure studies are usually somewhat difficult for regulatory review. The knowledge and expertise required for this requires a thorough understanding of animal and human immunology as well as specific product characteristics, including mechanism of action, antibody assays and assessment of results in a given clinical context. The appropriate interpretation of immunogenicity data is of critical importance for defining the safety profile of a monoclonal antibody. Two case studies described in this paper were prepared to mimic a real situation in which regulators need to evaluate immunogenicity studies conducted by manufacturers of monoclonal antibody products. The specific objective of the case studies was to illustrate assessment of unwanted immunogenicity and the important factors that need to be considered in this context. Regulators and manufacturers who attended the World Health Organization (WHO) implementation workshop on Evaluation of Biotherapeutic Products, held in Seoul, Republic of Korea, in May 2014, participated in the case studies and provided valuable input. This article outlines the main aspects of immunogenicity discussed in these case studies and a summary of the lessons learned at this occasion.